Epistemological Issues in the Theory of Equality of Opportunity - John E. Roemer (Public Reason)
EOp (Equality of opportunity) is an algorithm for measuring the degree of opportunity equality in a society. The researcher must identify the kind of advantage of concern (e.g., income , life expectancy, wage earning capacity), and what circumstances are important. She then partitions society into types, where each type consists of persons with approximately equal circumstances. The set of feasible policies must be delineated. If income is the kind of advantage under study, policies consist of different income tax functions. The algorithm holds people responsible for their effort, but not responsible for their circumstances. Compatibilism is discussed, as is the concept of an age of moral consent. Children, who have not reached the age of moral consent, are responsible for neither their nature nor their nurture. The scope of EOp requires us to recognize that EOp concerns itself with treating those are competing for social positions fairly, but does not address the issue of justice among those who consume what those competitors produce. Both are important.